Automation and seafarers : is this a ‘killer’ or ‘evolution’ in the context of seafaring profession? - Chan, Nicol Jia Hao (Nanyang Technological University, 2020)
With the increasing rate of advancement in today‟s technology, the shipping industry will not be left out. IMO has already rolled out guidelines to four degrees of automation where the highest level incorporates the adoption of fully autonomous ships. As the maritime industry transitions toward higher levels of automation, the seafarers will be directly impacted. Many jobs in today‟s world have undergone disruptions or evolutions, with higher levels of automation coming into the maritime industry the roles and skillsets of seafarers could see a dramatic change in dynamics. As such, the training elements of seafarers will play a huge role in determining their success in staying relevant in the industry after the adoption of higher technology. This paper seeks to explore the skillsets seafarers will need in the future to stay relevant. Also, this paper wishes to understand the training procedures and curriculums of training institutes. The combination of both factors will contribute to determining if automation will be a killer or evolution to the seafaring profession based on the quality of training they can receive.